Meaningful Inconsistencies : Bicultural Nationhood, the Free Market, and Schooling in Aotearoa/New Zealand. - Doerr, Neriko Musha (Studies in Public and Applied Anthropology, 6, 2009)
In the late twentieth century, the categorization of individuals in ethnic terms, affected by neoliberal reforms and the prioritization of market forces, has transformed our institutions and wreaked havoc around the world. Especially stark in societies that recognize their bi- or multicultural make-up, such categorization influences how individuals view themselves and are viewed by others in the educational arena. A small town in Aotearoa/New Zealand, with its contemporary shift toward official biculturalism and extensive free-marketization of schooling, is a prime example. This important volu.